2018
DOI: 10.1093/aob/mcy087
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the dynamic photosynthome

Abstract: BackgroundPhotosynthesis underpins plant productivity and yet is notoriously sensitive to small changes in environmental conditions, meaning that quantitation in nature across different time scales is not straightforward. The ‘dynamic’ changes in photosynthesis (i.e. the kinetics of the various reactions of photosynthesis in response to environmental shifts) are now known to be important in driving crop yield.ScopeIt is known that photosynthesis does not respond in a timely manner, and even a small temporal ‘m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
85
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(86 citation statements)
references
References 181 publications
(252 reference statements)
1
85
0
Order By: Relevance
“…To understand the reasons underlying this surprising assertion one also has to appreciate the processes and the rationale that underlies the regulation of leaf photosynthesis, partly covered in the NPQ mechanism described above. Central to this, is the coordination of ATP and NADPH formation with the metabolic activity of the Calvin cycle and the limitation of the production of ROS (Kaiser et al , ; Murchie et al , ). For this to occur, the energy supply to the ETC (from PSII and PSI) must be proportional to the capacity for its use.…”
Section: Quantifying the Role Of Npq In Plant Productivity: Diversitymentioning
confidence: 99%
See 1 more Smart Citation
“…To understand the reasons underlying this surprising assertion one also has to appreciate the processes and the rationale that underlies the regulation of leaf photosynthesis, partly covered in the NPQ mechanism described above. Central to this, is the coordination of ATP and NADPH formation with the metabolic activity of the Calvin cycle and the limitation of the production of ROS (Kaiser et al , ; Murchie et al , ). For this to occur, the energy supply to the ETC (from PSII and PSI) must be proportional to the capacity for its use.…”
Section: Quantifying the Role Of Npq In Plant Productivity: Diversitymentioning
confidence: 99%
“…The events just described can occur on a second‐by‐second basis. By comparison, a leaf held for several minutes in the same conditions will often demonstrate a statistically unchanging rate of gas exchange, NPQ and electron transport, the so‐called ‘steady state’ (Murchie et al , ). It has been suggested that this represents optimal photosynthesis whereas a change in rate represents a suboptimal rate (Kaiser et al , ).…”
Section: Quantifying the Role Of Npq In Plant Productivity: Diversitymentioning
confidence: 99%
“…In this section, various aspects of photosynthesis are discussed which require future attention in genetic mapping studies, but which impose serious challenges to phenotyping strategies. Photosynthetic responses due to environmental change are among those where most genetic variation is expected and novel traits are to be discovered (Lawson et al, ), but which are simultaneously the most difficult to properly track (Murchie et al ., ; Rungrat et al ., ).…”
Section: Challenges Of Phenotyping Photosynthesis‐related Traitsmentioning
confidence: 98%
“…The identification of functional allelic variations of important genes and traits related to photosynthesis using a forward genetics analysis of diversity panels is therefore a valuable approach, for three main reasons. First, the study of natural variation offers key insights into regulatory processes of photosynthesis, for example under fluctuating light conditions (Lawson et al ., ; Murchie et al ., ). Furthermore, genetic variation in the core genes of photosynthesis has been acknowledged to be an important resource for the bio‐engineering of improved photosynthesis (Prins et al ., ; Reeves et al ., ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation